DIPTEROCARPACEAE INVENTORY AT KETAMBE RESEARCH STATION, GUNUNG LEUSER NATIONAL PARK - Essy Harnelly; Iqbar .; Fauziah .; Agus Sara; Nir Fathiya; Rizky Amelia (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2016)
This research was about Dipterocarpaceae inventory at Ketambe Research Station, Gunung Leuser National Park. The research was done on July 2015. Determination of sampling plot was using purposive sampling. The parameter observed was species as well as number of species. The result showed that there were 5 species of Dipterocarpaceae found in the sampling plot. All the species found were belongs to tribe of Shoreae namely; Shorea johorensis, Shorea parvifolia, Hopea dryobalanoides, Shorea lepidota, and Parashorea lucida.Key words: Dipterocarpaceae, inventory, Gunung Leuser National Park